Tratamento de resíduos químicos gerados em laboratórios didáticos - uma revisão sobre a gestão, tratamento e disposição final - Quatroni, Felipe Domingues (Universidade Federal de São Carlos, 2025)
Chemical waste consists of substances discarded after use in laboratory, industrial, or academic processes. Due to characteristics such as toxicity, corrosiveness, and flammability, proper management is essential to ensure safety and environmental preservation. Regulations such as the National Solid Waste Policy (PNRS), resolutions of the National Environmental Council (CONAMA), standards of the National Health Surveillance Agency (ANVISA) and technical guidelines of the Brazilian Association of Technical Standards (ABNT) establish directives for classifying, handling, and properly disposing of these materials. Improper disposal can contaminate soil, water, and air, affecting ecosystems and posing risks to human health. Therefore, it is essential to adopt effective measures to minimize these impacts. Managing chemical waste involves key steps such as segregation, temporary internal and external storage, labeling, transportation, and final disposal. Some low-risk waste, such as certain soluble salts and diluted solutions, can be disposed of in the sink or regular trash, provided they meet environmental standards. However, other types require prior treatment to reduce their hazard. Acids and bases must be neutralized, toxic metals must be precipitated to prevent contamination, and oxidizing agents should be reduced due to explosion risks. Hazardous organic compounds, such as aldehydes and phenols, can be degraded to lower their toxicity. Highly toxic or environmentally persistent waste, such as halogenated solvents and hard-to-degrade substances, must be sent for incineration and destroyed at high temperatures. Unidentified waste is another challenge that makes management more complex and dangerous. In such cases, preliminary tests are necessary to determine their physical and chemical properties, ensuring a safe and appropriate final dispose Proper chemical waste management is essential to reduce environmental impacts and ensure laboratory safety. Following technical standards, complying with environmental regulations, and investing in awareness and training are fundamental measures for responsible disposal, promoting a more sustainable and secure environment.
Treatment of chemical waste generated in educational laboratories
Keywords: Resíduos químicos; Preservação ambiental; Tratamento de resíduos; Disposição final; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL